Determination of Cisplatin and Carboplatin Anticancer Drugs by Non-suppressed Ion Chromatography with an Inductively Coupled Plasma Atomic Emission Detector. (3rd May 2018) - Zachariadis, George A.; Misopoulou, Ourania E.
ABSTRACT: Two non-suppressed ion chromatographic (IC) methods, one with an anion and one with a cation separation column, were investigated for first time to determine cisplatin and carboplatin anticancer drugs using inductively coupled plasma–atomic emission spectrometry as a detector. The Shodex IC YK-421 (4.6 × 125 mm 2 ) column was considered as the preferred separation column. The mobile phase in this case consisted of tartaric acid and boric acid. The flow rate was 1 mL/min and the injection volume was 20 μL. Separation was carried out in about 2 min with column temperature at 30°C after optimization. With cationic separation, the cisplatin elutes first, as opposed to the anionic one, where it elutes second. In addition, with both columns, a second peak for cisplatin appears which is attributed to a hydrolysis product of the drug. For the cation chromatographic method, the repeatability ranged from 3.1 to 5.9%, whereas the inter-day precision was 13.3 and 16.3% for cisplatin and carboplatin, respectively. The detection limits were 0.1 mg/ L Pt for both compounds. The proposed method was applied to the analysis of human urine with satisfactory recoveries indicating that there are no matrix effects.